How do you solve #2x - y = 3# and #3x - y = 4# using substitution?

1 Answer
May 1, 2016

Answer:

An alternative method of solving them.
#x = 1 and y = -1#

Explanation:

Both of these equations contain the single variable #y#.
Transpose them to make #y# the subject.

#y = 3x - 4# ....... and ....... #y = 2x - 3#

Now, because # y = y#, it follows that

.................#3x - 4 = 2x - 3# (giving an equation with one variable)

Solving it gives: #x = 1#

There are now two ways to calculate the value of #y#

#y = 3(1) -4# = -1 and #y = 2(1) - 3# = -1